Smoking as a risk factor for psychosomatic disorders in medical students - Marina A. Sergeeva; Talgat B. Kulushev; Larisa A. Kostina; Aliya S. Kubekova; Veronika P. Mamina (Elementary Education Online, 2023)
The article analyzes smoking as a risk factor for psychosomatic disorders in medical students. The obtained results obtained indicate the highest prevalence of psychosomatic disorders among fourth-year students and neurotic reactions caused by the conditions of training, and indicate the need for psychological support and psycho-preventive measures. Positive correlations were found between neurotic reactions in students, the level of depression and smoking. The higher the level of neurotic disorders among students, the higher their assessment of their own depression, and the destructive coping strategy of smoking is characteristic of them. These respondents tend to concentrate on unpleasant emotions and actively express them. Correlation relationships between the level of psychosomatic disorders and such coping strategy as “smoking” among students were revealed. When developing psychological support programs and prevention programs, one should take into account the relationship between smoking and psychosomatic disorders in students, as well as when organizing a health-preserving educational environment of the university